2010
DOI: 10.1088/0960-1317/20/8/085001
|View full text |Cite
|
Sign up to set email alerts
|

Specimen alignment in an axial tensile test of thin films using direct imaging and its influence on the mechanical properties of BeCu

Abstract: This paper proposes a new system for verification of the alignment of loading fixtures and test specimens during tensile testing of thin film with a micrometer size through direct imaging. The novel and reliable image recognition system to evaluate the misalignment between the load train and the specimen axes during tensile test of thin film was developed using digital image processing technology with CCD. The decision of whether alignment of the tensile specimen is acceptable or not is based on a probabilisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Alternatives are electro-static clamping [53] and mechanical locking via pin-in-hole [54] or geometries that conform to the gauge-end [55]. However, in all cases careful provisions for specimen alignment are necessary [56][57][58][59][60][61][62]. Transverse and rotational misalignment may occur between the specimen's longitudinal axis and the setup's loading axis.…”
Section: Design Principlementioning
confidence: 99%
See 2 more Smart Citations
“…Alternatives are electro-static clamping [53] and mechanical locking via pin-in-hole [54] or geometries that conform to the gauge-end [55]. However, in all cases careful provisions for specimen alignment are necessary [56][57][58][59][60][61][62]. Transverse and rotational misalignment may occur between the specimen's longitudinal axis and the setup's loading axis.…”
Section: Design Principlementioning
confidence: 99%
“…However, reported results typically do not state what precision of alignment is needed and actually attained, with some notable exceptions. In [62] image processing has been employed to measure the rotational misalignment. Adequate alignment can also be established through repeated elastic loading and alignment adjustment until a maximum of the measured modulus is obtained [59].…”
Section: Design Principlementioning
confidence: 99%
See 1 more Smart Citation
“…In the tensile test, it has been shown that bending stresses that inadvertently occur due to misalignment between the applied force and the specimen axes during testing can affect the test results. Therefore, the authors developed a novel and reliable image recognition system to evaluate the misalignment between the load-train and the specimen axes during the tensile test of the thin films by using a digital image processing technology with a CCD [13] developed image recognition system was adopted to secure a good alignment between the applied force and the specimen axes. Before mounting the specimen on jigs, the misalignment between the jig of the loadcell side and the jig of the actuator side was inspected using the system, Fig.…”
Section: Micro Tensile Testsmentioning
confidence: 99%
“…As mechanics researchers, we focus on the characterization of their mechanical properties, which are important factors affecting not only their performance but also the basis to analyze their reliabilities. Estimation of fundamental mechanical property requires that displacements and strains be measured at micron and submicron length scale [1][2][3][4][5], which means traditional macroscopic experimental testing methods like moiré method and digital image correlation (DIC) method are no longer applicable and it is urgent to develop novel microscopic testing methods.…”
Section: Introductionmentioning
confidence: 99%